Current Climate Changes - Ambrizzi, Tercio; Rehbein, Amanda (Cadernos de Astronomia, 2025)
Human development, which began around 300,000 years ago, has always occurred in parallel with natural climate variations. However, since the Industrial Revolution, human action has intensified the greenhouse effect, raising the average global temperature and altering weather patterns, resulting in severe impacts such as rising temperatures, changes in precipitation patterns and an increase in the frequency of severe weather events such as storms, tornadoes and hurricanes. This article explores the main current climate changes and how they are monitored through the analysis of historical data. In addition, it presents projections from climate models that allow us to anticipate future scenarios, including rising temperatures and changes in precipitation patterns, especially in South America. Finally, the text highlights the importance of concrete actions to mitigate greenhouse gas emissions, responsible for current climate change, using technologies already available. We conclude that, in order to face the climate emergency, it is essential to integrate Brazil’s human and natural resources, combined with scientific knowledge, in order to implement effective solutions to reduce impacts and protect the most vulnerable populations.
Keywords: climate change; global warming; climate projections; South America; mitigation